Genetic analysis of lactation curves in buffaloes, using Wood's model - Marques de Carvalho, Ludmilla A.; Moura, Guilherme F. de; Vieira, Dheynne A.; Hurtado-Lugo, Naudin A.; Aspilcueta-Borquis, Rusbel R. [UNESP]; Gomide, Ana P. C.; Tonhati, Humberto [UNESP]; Oliveira, Henrique N. de [UNESP]; Araujo-Neto, Francisco R. de (Spanish Natl Inst Agricultural & Food Research & Technolo, 2020)
Aim of study: To estimate the heritability and genetic correlations for lactation curve traits in buffaloes. Area of study: The buffalo cows were raised on properties located in the states of Sao Paulo, Ceara and Rio Grande do Norte, Brazil. Material and methods: The individual parameters of Wood's model (theta(1), theta(2), and theta(3)) were obtained using a non-linear mixed model. Peak yield (PY), peak time (PT) and lactation persistency (LP) were also calculated. These individual parameters were employed in multi-trait analysis with the milk yield (MY) using Bayesian inference. Main results: The heritability estimates were of low to moderate magnitudes, with values ranging from 0.156 (theta(2)) to 0.299 (PY). The estimates for genetic correlation between the Wood's parameters and MY were of low to high magnitude and ranged from -0.533 (theta(2) and MY) to 0.983 (PY and MY). Research highlights: The heritability estimates obtained indicate that the traits studied can be used in animal breeding programs.
Keywords: Bubalus bubalis; milk yield; peak lactation; persistency